Il comprendere in educazione - Travaglini, Roberto (Studi sulla Formazione/Open Journal of Education, 2025)
The article examines the cognitive process underlying understanding in the educational environment, starting from a neo-cognitivist assumption of Gardnerian inspiration, according to which such a process, in disagreement with a now anachronistic passive vision of the mind (all behaviourist), produces an important inner transformation: understanding (both of the teacher and the student) involves specific, as well as complex theoretical-operational and strategic-methodological dynamisms adopted during didactic communication, such that a cognitive leap of knowledge can be made in view of the realization of a metacognitive process. For this reason, we hope for a reform of thought (Morin) that proposes a new and different conception of what can be called knowledge far from an undifferentiated accumulation of information devoid of any organic and functional location, to didactically build a well-made head instead of a well-filled head, generated by a motivation to know that represents the expression of quality factors within the training process and that is intrinsic, because it derives from the pleasure of carrying out cognitive activities capable of involving the individual as a whole.